Analisis Wacana Kritis Pengajuan Gugatan Badan Kemenangan Nasional (Bpn) Ke Mahkamah Konstitusi (Mk) Pada Artikel Media Daring Tirto.Id - Azzahra Maulida Tantri Goserira (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2019)
Pemilu become one of the best time for the media to voice issues to the public. Behind the news, the media is trying to build discourse to be enjoyed by the wider community. This study raises the reporting of the newspaper with the theme "Filing a National Victim Body (BPN) Lawsuit to the Constitutional Court (MK)" which was analyzed using the Critical Discourse Analysis of the Van Dijk Model. In his analysis, Van Dijk emphasized on three aspects, namely macro structure, superstructure and micro structure. the subject observed was the online media Tirto.id with the object of discourse built by the online media regarding reporting electoral fraud to the Constitutional Court by BPN in the political rubric on online media. Tirto.id raised the title "Vote Difference of 16.9 Million, Can Prabowo Win a Lawsuit in the Court?" The results obtained by Tirto.id developed three discourses namely; 1. The severity of the possibility of BPN winning a lawsuit to the Constitutional Court regarding fraud in the 2019 elections, 2. Jokowi-Ma'ruf's victory was a landslide victory, making it difficult to be ousted. 3. The optimism of the BPN in filing a lawsuit to the MK has no effect on TKN. In the aspect of Social Cognition, Tirto.id claims to stand above and for all groups, as well as non-partisans. Tirto.id prioritizes interviews as news writing material. So that the alignments that appear on the writer sourced from interviews with certain figures.